Pembuatan Aplikasi Sistem Informasi Administrasi dan Pemesanan Online Berbasis Web Pada Travel X - Levi Julius Liumanta; Silvia Rostianingsih; Djoni Haryadi Setiabudi (Jurnal Infra, 2016)
Administration system in Travel X still using manually all of the business process likely record a reservation in a document. With that condition make Travel X need more time to get information, generating report and high risk to lost document. Therefore, Travel X needed system to accomodate administration quickly and preciesly. According to the analysis based on Travel X problems, an application to support the Travel X business performance must be made.The application would be implemented to process the passanger reservation, package reservation, online reservation and also generating report. The design of the Data Flow Diagram and the ERD uses Power Designer 16.5 The application will be based on CodeIgniter Framework and MySQL for the database.User satisfaction towards the application’s overall quality is 42% good responds and 28% very good responds which means the application has fulfilled and corresponds to the system requirements. This application can records process by automate passanger reservation or online reservation.